2015
DOI: 10.1080/1540496x.2015.1026696
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and Productivity in Services: Evidence from Chile

Abstract: Artículo de publicación ISISin acceso a texto completoWe analyze empirically the firm-level relationship between innovation and productivity in the Chilean service sector using the manufacturing sector as a benchmark. We find that manufacturing and service industries have similar determinants of the probability of introducing technological innovations. We also find a positive effect of technological and nontechnological innovation on labor productivity for both sectors. However, there are some differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 24 publications
1
33
0
5
Order By: Relevance
“…In the case of Chile, previous contributions have focused on the links between i) innovationproductivity growth (Benavente, 2006;Alvarez et al, 2010Alvarez et al, , 2012 and ii) innovation-employment growth (Benavente and Lauterbach, 2008;Alvarez et al, 2010). Regarding the innovationproductivity growth relation for manufacturing firms, Benavente (2006) finds no positive and significant effect of innovation on productivity growth while Alvarez et al (2010) show that product innovation has a significant effect on productivity two years after its introduction but no simultaneous effect.…”
Section: Related Literaturementioning
confidence: 95%
See 2 more Smart Citations
“…In the case of Chile, previous contributions have focused on the links between i) innovationproductivity growth (Benavente, 2006;Alvarez et al, 2010Alvarez et al, , 2012 and ii) innovation-employment growth (Benavente and Lauterbach, 2008;Alvarez et al, 2010). Regarding the innovationproductivity growth relation for manufacturing firms, Benavente (2006) finds no positive and significant effect of innovation on productivity growth while Alvarez et al (2010) show that product innovation has a significant effect on productivity two years after its introduction but no simultaneous effect.…”
Section: Related Literaturementioning
confidence: 95%
“…Regarding the innovationproductivity growth relation for manufacturing firms, Benavente (2006) finds no positive and significant effect of innovation on productivity growth while Alvarez et al (2010) show that product innovation has a significant effect on productivity two years after its introduction but no simultaneous effect. Alvarez et al (2012) found that for both sectors technological innovation appears as an important determinants of labor productivity. Concerning innovation and employment growth, the evidence suggests that process innovation is generally found not to be a determinant of employment growth in Chilean manufacturing plants while product innovation is positively associated with an expansion of employment (Benavente and Lauterbach, 2008;Alvarez et al, 2010).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that higher levels of investment in innovation (notably in R&D) lead to a higher propensity to introduce technological innovation in firms from Argentina (Arza and Lopez, 2010;Chudnovsky et al, 2006), Brazil (Correa et al, 2005;Raffo et al, 2008), and Bulgaria (Stoevsky, 2005). On the other hand, results from Chile (Alvarez et al, 2010;Benavente, 2006) and Mexico (Perez et al, 2005) do not support this finding (Crespi and Zuniga, 2012). Focusing on a panel of 27 transition and 20 Western European countries between 1990 and 2006, Krammer (2008) found that domestic efforts and investment in R&D had a deeper effect for the Western European countries than the Eastern ones, since the latter had inherited at the beginning of the 1990s an outdated R&D stock, specialised in mature, heavy industries with little potential for innovation and productivity growth.…”
Section: Research In Low-and Middle-income Countriesmentioning
confidence: 99%
“…Some studies demonstrate that service sector is as innovative as the manufacturing sector -for instance, Álvarez, Bravo-Ortega and Zahler (2015), which analysed 7192 Chilean companies, Carvalho, Costa and Caiado (2013) that focused on 4504 Portuguese companies, Evangelista and Vezzani (2010) and Sirilli and Evangelista (1998) that examined Italian companies, or Forsman (2011) which explored the types of innovations developed in small Finnish manufacturing and service companies. Other studies found evidence that service companies have low propensity to innovate (López & Ramos, 2015), and fall behind their manufacturing counterparts as to innovation performance (Tacsir, 2011;Zahler, Iacovone, & Mattoo, 2014).…”
Section: Introductionmentioning
confidence: 99%